Effect Of Levels And Sources Of Protein On The Performance And Nutrient Digestibility In Black Bengal Goat (Bangladesh Journal of Animal Science, 2012)
Sixteen castrated male Black Bengal goats (aged between 8 and 10 months and average live weight 9.16 kg) were used in a 2 × 2 factorial design to study the effect of protein levels and sources on growth and nutrient digestibility under intensive condition for 56 days. The sources of protein were mustard oil cake (MOC) and soybean meal (SBM). Level of protein in each sources were 22 (HP-high protein) and 16 (LP-low protein) percentage. The dietary treatments were (T1) MOC-HP, (T2) MOC-LP, (T3) SBM-HP and (T4) SBM-LP. Concentrate diets as well as dal grass was fed throughout the experimental period and last week considered for digestibility trial. Average daily live weight gain of goats was 42, 41, 43, and 52 g for the diets T1, T2, T3 and T4 respectively. The result showed no significant (P>0.05) variation between protein sources and their levels on growth performance. Intake of DM was 425, 389, 407 and 437 g/d which were 4.2, 3.8, 4.0 and 4.1 percent of their body weight for the diets T1, T2, T3 and T4 respectively. Intake of CP was 59, 46, 56 and 50 g/d respectively. The sources of protein did not influence the intake of CP (P>0.05), but their levels had (P